IMPLEMENTATION OF GOOD GOVERNANCE PRINCIPLES IN THE PROVINCIAL GOVERNMENT OF ACEH: CHALLENGES AND OPPORTUNITIES - Nurul Sapna Joetry (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2024)
This study examines the implementation of good governance principles in the Provincial Government of Aceh, a region with unique post-conflict dynamics and special autonomy. Using a mixed-methods design that integrates qualitative interviews with officials, civil society actors, and community leaders alongside quantitative surveys, the research explores three key dimensions: transparency, accountability, and public participation. Findings reveal persistent challenges, including limited citizen access to policy information, weak participatory mechanisms, and recurring corruption cases that undermine institutional integrity. At the same time, promising opportunities emerge through digital innovations in public service delivery and growing collaboration between government and civil society. These developments demonstrate the potential of technology and inclusive governance practices to enhance transparency, rebuild trust, and foster sustainable development. The study contributes to the limited literature on governance in Aceh by offering an integrated analysis of both challenges and reform prospects. Recommendations emphasize comprehensive bureaucratic reform, capacity building, and participatory policymaking as critical steps for strengthening governance in post-conflict and autonomous regions.